Relationship between the Expression of RASSF1A Protein and Promoter Hypermethylation of RASSF1A Gene in Bladder Tumor - 胡建庭 李宏召 史涛坪 马鑫 王保军 徐华 艾星 居正华 王超 张国玺 张旭 (Journal of Huazhong University of Science and Technology. Medical sciences, 2008)
To investigate the relationship between the expression of RASSF1A protein and promoter hypermethylation of RASSF1A gene, RASSF1A protein expression was measured by Western blotting in 10 specimens of normal bladder tissues and 23 specimens of bladder transitional cell carcinoma （BTCC）. The promoter methylation in BTCC and normal bladder tissues was detected by methylation-specific PCR （MSP）. The results showed that the expression level of RASSF1A protein was significantly lower in BTCC tissues than that in normal bladder tissues. However, it was not correlated with its clinical stages and pathological grades. The frequency of promoter methylation of RASSF1A gene was higher in BTCC tissues than that in normal bladder tissues. In 14 patients with the aberrant promoter methylation, 13 showed loss or low expression of RASSF 1A protein. It is concluded that RASSF1A gene promoter methylation may contribute to the low level or loss of RASSF1A protein expression, the inactivation of RASSF1A gene and the genesis of BTCC. But, it may bear no correlation with its clinical stages and pathological grades.